Performance of osteoporosis self-assessment tool in detecting low bone mineral density in menopausal women - Haryono, Ignatio Rika; Prastowo, Nawanto Agung (Faculty of Medicine, Trisakti University, 2017)
BackgroundThe osteoporosis self-assessment tool (OST) is a simple screening tool to assess risk of osteoporosis and to select high risk women for dual-energy x-ray absorptiometry (DXA) examination. This study aimed to evaluate OST performance in detecting low bone mineral density (BMD) in menopausal women.MethodsA cross-sectional study involving 60 menopausal women aged 50-65 years. The OST score was calculated from: [weight (kg) – age (yr)] x 0.2. Subjects were classified by OST score into low risk (OST ³2) and high risk (OST< 2) groups. BMD was determined by DXA at 3 bone locations (L1-L4, femoral neck, and total hip). DXA T-scores were categorized into: normal BMD (T-score >-1) and low BMD (T-score £-1). Independent t-test was used to compare subject characteristics between OST groups. Diagnostic performance of OST was evaluated by measuring sensitivity, specificity, positive & negative predictive value (PPV, NPV), positive & negative likelihood ratio (PLR, NLR) and receiver-operating characteristic (ROC). Significance was set at p<0.05.ResultsSubject characteristics and BMD between groups were significantly different (p<0.05). Most subjects (44/73.3%) had high risk of low BMD (OST < 2). Low BMD (T score £-1) was found in 43 subjects (71.7%) at L1-L4, 41 subjects (68.3%) at femoral neck, and 37 subjects (61.7%) at total hip. Diagnostic performance of OST was significant at total hip BMD (sensitivity=0.946, AUC=0.777).Conclusion We conclude that use of the OST score in menopausal women is effective and has adequate sensitivity and specificity. The highest diagnostic performance of OST is on total hip BMD.